Genetic-based evaluation of management units for sustainable vendace (Coregonus albula) fisheries in a large lake system - Karjalainen Juha; Sjövik Rosanna; Väänänen Tuula; Sävilammi Tiina; Sundberg Lotta-Riina; Uusi-Heikkilä Silva; Marjomäki Timo J. (ELSEVIER, 2022)
The goal of the processing industry, trade and consumers is to get eco-labelled freshwater fish products from sustainable fisheries into the market as soon as possible. The fourth largest natural lake system in Europe, the Saimaa lake system supports a fishery for vendace (Coregonus albula). Certification of the fishery requires an understanding of population structure to help determine the number and spatial extent of management units. In this study, we analysed the genetic diversity of local vendace populations in the Saimaa lake system and aimed to identify the conservation and management units of vendace. Within the Saimaa, the genetic divergence between local populations of vendace was weak and their genetic divergence did not follow an isolation by geographic distance pattern. Vendace has potential to disperse effectively within and between local populations in different lake basins. Even if we observed subtle genetic divergence within our study systems, available information showed no significant evidence that the local populations had unique evolutionarily significant traits. The local populations of the Saimaa lake system seem to have similar life history and morphological traits as in the whole Central Finland lake district. The conservation of genetic diversity seemed not to require basin-specific actions and we conclude that management of local vendace populations of Saimaa as one management unit is advisable.